Impact of phenylketonuria type meal on appetite, thermic effect of feeding and postprandial fat oxidation. Issue 3 (June 2018) - Alfheeaid, Hani; Gerasimidis, Konstantinos; Năstase, Ana-Maria; Elhauge, Mie; Cochrane, Barbara; Malkova, Dalia
Summary: Background: Dietary management of phenylketonuria (PKU) requires the replacement of natural protein-containing foods with special low protein foods. The effect of a PKU type diet on factors contributing to energy balance requires investigation. Objective: To investigate the impact of a PKU type meal on appetite ratings, gut appetite hormones, thermic effect of feeding (TEF) and fat oxidation. Methods: Twenty-three healthy adults (mean ± SD age: 24.3 ± 5.1 years; BMI: 22.4 ± 2.5 kg/m 2 ) participated in a randomized, crossover design study. Each participant conducted two (PKU and Control) experimental trials which involved consumption of a PKU type meal and protein substitute drink or an isocaloric and weight matched ordinary meal and protein-enriched milk. Appetite, metabolic rate, fat oxidation measurements and blood collections were conducted for the duration of 300 min. On the completion of the measurements ad libitum buffet dinner was served. Results: Responses of appetite ratings, plasma concentrations of GLP-1 and PYY ( P > 0.05, trial effect, two-way ANOVA) and energy intake during ad libitum buffet dinner ( P > 0.05, paired t -test) were not significantly different between the two trials. The TEF (PKU, 10.2 ± 1.5%; Control, 13.2 ± 1.0%) and the total amount of fat oxidized (PKU, 18.90 ± 1.10 g; Control, 22.10 ± 1.10 g) were significantly ( P < 0.05, paired t -tests) lower in the PKU than in the Control trial. The differences in TEF and fat oxidation were significant ( P < 0.05, paired t -tests) for the post-meal period. Conclusions: Consumption of a meal composed of special low protein foods has no detrimental impact on appetite and appetite hormones but produces a lower TEF and postprandial fat oxidation than an ordinary meal. These metabolic alterations may contribute to the increased prevalence of obesity reported in patients with PKU on contemporary dietary management. Clinical trial registration : The trial has been registered in ClinicalTrials as NCT02440932 .